2022
DOI: 10.1186/s12920-022-01383-w
|View full text |Cite
|
Sign up to set email alerts
|

CD44 is a prognostic biomarker and correlated with immune infiltrates in gastric cancer

Abstract: Objective Gastric carcinoma is the most common malignant tumour of the human digestive system worldwide. CD44 serves as a marker for several tumour stem cells, including gastric cancer. However, the prognostic value of CD44 and its correlation with immune infiltration in gastric cancer remain unclear. Methods The relative expression level of CD44 RNA in gastric cancer was analysed in the TCGA and GEPIA2 databases and validated in the GEO database. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…Among them, we found that CD44 might be a good candidate since the latter was a well-known target of the SWI/SNF complex [ 28 ] and a proven marker of gastric cancer stem cells (GCSCs) [ 29 , 30 ], associated with proliferation of gastric epithelial cells [ 31 ]. Furthermore, CD44 was also known to be closely related to cell invasiveness and poor prognosis of GC [ 32 ]. Thus, using ChIP assay, we explored that PHF10, one catalytic subunit of the SWI/SNF complex (BRG1) and two core regulatory subunits (BAF155 and SNF5) could all bind to promoter of CD44 gene in two different cell lines of GC (SGC7901 and MKN28).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, we found that CD44 might be a good candidate since the latter was a well-known target of the SWI/SNF complex [ 28 ] and a proven marker of gastric cancer stem cells (GCSCs) [ 29 , 30 ], associated with proliferation of gastric epithelial cells [ 31 ]. Furthermore, CD44 was also known to be closely related to cell invasiveness and poor prognosis of GC [ 32 ]. Thus, using ChIP assay, we explored that PHF10, one catalytic subunit of the SWI/SNF complex (BRG1) and two core regulatory subunits (BAF155 and SNF5) could all bind to promoter of CD44 gene in two different cell lines of GC (SGC7901 and MKN28).…”
Section: Discussionmentioning
confidence: 99%
“…In line with our findings, GDF15 promotes the immune escape of ovarian cancer by targeting CD44 in dendritic cells ( 46 ). CD44 correlates with immune infiltrates in gastric cancer ( 47 ). Besides, IL18 increases the immune escape of gastric cancer by downregulating CD70 and maintaining CD44 ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…The conversion of CD44s to CD44v promotes tumorigenesis 26 . High CD44 expression was observed in gastric cancer, and its expression correlates with immune cell infiltration 27 . Zyxin is also involved in immune cell infiltration in ulcerative colitis 28 .…”
Section: Discussionmentioning
confidence: 99%